A Modified Hill Cipher For Better Security - Johni S Pasaribu (Journal of International Conference Proceedings (JICP), 2018)
Security is the most challenging aspects in the internet and network application. These days the applications like Internet and networks are growing very fast, thereby the importance and the value of the exchanged data over the internet or other media types are increasing. While transmitting any confidential information across network, some unauthorized user tend to steal or corrupt the data. To prevent this interruption, security of data is needed. As data security is needed for protecting data from unauthorized users and destructive forces, some security techniques are used. Encryption is one such technique which is used to protect the database from unauthorized accesses and unwanted actions of external clients. It is used to secure the confidential information from unauthorized user by converting the data in to that format that is only understandable by the authorized receiver that knows the respective decryption to obtain the original data or information. In this paper, our focus will be on Database Security, as databases are considered as the storehouses of data. Generally, data of an organization or a company is stored in databases and is very crucial to the organization. Today, most of the organizations allow their clients to use their services (online banking, online shopping etc) by accessing their databases. This leads to a requirement of high level security to deal with information attackers. An information attacker tries to illegally acquire or modify the highly confidential data of the organization. An innovative approach for database security using Hill Cipher encryption & decryption method is proposed. This cryptography based approach provides an additional level of security to the database systems. Important data or information crucial to the organization should be secured from illegal theft and attacks. This encryption scheme completely is based on key matrix that a organization decides before encryption and decryption. In this proposed scheme a common key is used to encrypt the data items. Keywords: Database, Data security, Encryption, Decryption, Hill Chiper Algorithm.